2015
DOI: 10.1007/s10342-015-0870-6
|View full text |Cite
|
Sign up to set email alerts
|

Shrub biomass accumulation and growth rate models to quantify carbon stocks and fluxes for the Mediterranean region

Abstract: The importance of shrub formations in the Mediterranean area both in terms of area occupied and carbon sequestered by them is currently being recognized. However, due to the lack of suitable models to estimate biomass accumulation and growth rate in this region, the carbon sequestered by these formations is not included when computing the total carbon stocks in aboveground biomass in Mediterranean forest ecosystems, according to the IPCC guidelines. The aim of the present study is to develop equations to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 49 publications
(40 reference statements)
1
42
0
1
Order By: Relevance
“…An increasing amount of research in recent years has been focused on estimating the carbon stocks in Mediterranean shrublands, mainly through the development of estimation tools (e.g., Navarro & Blanco, 2006;Corona et al, 2012;Ruiz-Peinado et al, 2013b;Botequim et al, 2014;Pasalodos-Tato et al, 2015). The importance of shrub layer will depend on the ecosystem considered, the shrub species and tree density among other factors.…”
Section: Shrub Layer Importancementioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of research in recent years has been focused on estimating the carbon stocks in Mediterranean shrublands, mainly through the development of estimation tools (e.g., Navarro & Blanco, 2006;Corona et al, 2012;Ruiz-Peinado et al, 2013b;Botequim et al, 2014;Pasalodos-Tato et al, 2015). The importance of shrub layer will depend on the ecosystem considered, the shrub species and tree density among other factors.…”
Section: Shrub Layer Importancementioning
confidence: 99%
“…National carbon estimations for Spanish shrublands have been conducted by Montero et al (2016) using models for different shrub associations (Pasalodos-Tato et al, 2015). The results suggest that aboveground shrub biomass accounts for more than 91 Tg C. This figure represents 8.2% of the tree carbon stock in Spanish forests (Montero & Serrada, 2013), highlighting the importance of including shrubland in carbon accounts.…”
Section: Shrub Layer Importancementioning
confidence: 99%
“…The inclusion of understory vegetation in carbon sequestration has been traditionally ignored [12] since it represents lower amounts of biomass compared with tree aboveground biomass (AGB). However, considering the global scale this amount constitutes an important pool for carbon sequestration [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In India, Singh and Lodhiyal (2009) also estimated the tree biomass and C allocation in an 8-year-old poplar plantation based on the same value of 47.5%. Subsequent analyses showed that C concentration can vary between different components within the same tree species, resulting in C ratios ranging from above to below 50% (Zheng et al, 2008;Tolunay, 2009;He et al, 2013;Pasalodos-Tato et al, 2015). The accuracy of C content assessments has been improved with estimations of C concentration in each tree component (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 96%